2019
DOI: 10.1021/jacs.8b11474
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Site-Binding Modes of Ions and Water to Nucleic Acids Using Molecular Solvation Theory

Abstract: Site binding of ions and water shapes nucleic acids folding, dynamics, and biological function, complementing the more diffuse, nonspecific "territorial" ion binding. Unlike territorial binding, prediction of site-specific binding to nucleic acids remains an unsolved challenge in computational biophysics. This work presents a new toolset based on the 3D-RISM molecular solvation theory and topological analysis that predicts cation and water site binding to nucleic acids. 3D-RISM is shown to accurately capture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 119 publications
5
69
0
Order By: Relevance
“…The role of non-specifically surface-bound ions in molecular biology is well documented. Thus, Ca 2+ and Mg 2+ ions non-specifically bind to backbone phosphate oxygen atoms of nucleic acid [10][11][12], and the binding reduces the electrostatic repulsion between adjacent phosphate groups, hence stabilizes pairing and base stacking [13,14]. The non-specifically surface-bound ions were found to be a key regulator for protein-protein binding and pH-dependence of the binding affinity [15], to affect ion-induced filament formation [16] and to alter macromolecular dynamics [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of non-specifically surface-bound ions in molecular biology is well documented. Thus, Ca 2+ and Mg 2+ ions non-specifically bind to backbone phosphate oxygen atoms of nucleic acid [10][11][12], and the binding reduces the electrostatic repulsion between adjacent phosphate groups, hence stabilizes pairing and base stacking [13,14]. The non-specifically surface-bound ions were found to be a key regulator for protein-protein binding and pH-dependence of the binding affinity [15], to affect ion-induced filament formation [16] and to alter macromolecular dynamics [17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other side of the spectra are computational models to predict positions of non-specifically surface-bound ions. To the best of our knowledge, the BION [21,22] is the only publicly available resource for predicting such type of ions (excluding recent work [12] which however does not provide web service), while many other predictors deal with specifically bound ions [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have used classical MD or other theoretical approaches to investigate Mg 2+ -RNA binding, but they were limited to native conformations due to their inability to overcome the issues associated with the Mg 2+ exchange rates (15)(16)(17)(18)(19)(20)(21). The exchange rate of water complexed to Mg 2+ is on the µs time scale (6.7 x 10 5 s -1 ) and the exchange rate of Mg 2+ with phosphate is on the ms time scale (0.5 to 2.5 x 10 3 s -1 ) (22), which is beyond the time scale of typical atomistic MD simulations (19,23) such that only limited insights into Mg 2+ -RNA interactions are accessible (24).…”
Section: Introductionmentioning
confidence: 99%
“…2,25 40 Recently, simulations of a large ribozyme and several other RNA constructs, in the presence of both monovalent and divalent ions, have shown that the ions have a strong propensity to bind to nucleotides in a site-specific manner, and not uniformly. [25][26][27] The irregular shape of the RNA plays an important role in determining where the ions bind, as the ions are naturally drawn to the highly negatively charged pockets.Other studies, focusing only on the folded states or well-defined complexes involving RNA, have shown 45 that the site-specifically bound Mg 2+ ions to various RNA molecules are stable. [28][29][30][31][32][33] These studies did not consider ion-driven folding of RNA from a completely unfolded state, which is the subject of our interest here and elsewhere.…”
mentioning
confidence: 99%
“…2,25 40 Recently, simulations of a large ribozyme and several other RNA constructs, in the presence of both monovalent and divalent ions, have shown that the ions have a strong propensity to bind to nucleotides in a site-specific manner, and not uniformly. [25][26][27] The irregular shape of the RNA plays an important role in determining where the ions bind, as the ions are naturally drawn to the highly negatively charged pockets.…”
mentioning
confidence: 99%